Застосування Agile-управління та Agile-маркетингу на підприємствах в міжнародному бізнесі - Чайкова, Олена Ігорівна; Подмокова, Анастасія Юріївна; Губанов, Павел Олегович (НТУ "ХПІ", 2018)
У статті розглядаються підходи Agile-управління на підприємствах. Наведено характеристики та риси Agile – гнучкої методології управління проектами. Визначено важливість застосування ключових показників ефективності для оцінки якості та швидкості виконання обов’язків персоналом в Agile. Відображена інформація щодо світових тенденцій застосування Agile-методів, динаміки змін показників. Виділені причини, які спонукають підприємства міжнародного бізнесу до впровадження Agile-управління. Розкрите визначення поняття Agile – маркетингу. Виокремленні відмінності принципів Agile-маркетингу від класичного маркетингу. Наведено приклади застосування Agile-підходу в маркетингу підприємствами світу.

In the article approaches of Agile-management at the enterprises are considered. The characteristics and features of Agile are presented - a flexible methodology for project management. The importance of applying key performance indicators to assess the quality and speed of staff responsibilities in Agile has been determined. The information on the world tendencies of application of Agile-methods, dynamics of changes of indicators is displayed. The reasons which induce the enterprises of the international business to introduction of Agile - management are allocated. The definition of the concept of Agile-marketing is disclosed. Differences in the principles of Agile-marketing from classical marketing are distinguished. Examples of application of the Agile approach in marketing by enterprises in the world are given.
Application of Agile-management and Agile-marketing at enterprises in international business
Keywords: еджайл-управління; ключові показники ефективності; проект; управління проектами; якість; key performance indicators